Thermal Performance of Horizontal Fixed Sun Shading Device - Gimat, Mohd Fadlullah; Mat Sulaiman, Mohd Khairul Azhar; Abd Malek, Mohd Iskandar; Mohd Nor, Mohd Farihan Irfan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Earlier investigations on passive cooling methods applied software modelling, and the findings were not confirmed through field measurement. Hence, this study applied a stationary experiment on a real structure and weather conditions employing horizontal sun shading (SDH). The purpose of this study was to compare the performance of fixed passive sun-shading devices put on to the bare façade of three-story terrace shophouses in Malaysia. The experiment findings revealed that SDH significantly improved the internal thermal environment by lowering the average monthly indoor air temperature (Ta) by 0.98 K and the peak temperature by 2.11 K. SDH is also effective during the warmest sunny days, lowering 1.23 K on average for the day. Meanwhile, SDH reduced the temperature in the control room by 5.40 K during the warmest peak time. When it came to indoor mean radiant temperature (Tmrt), SDH performed better than the control room in the very hot peak over a month (2.38 K) and on the highest temperature of the day (7.70 K). Finally, it can be inferred that SDH worked better from late at night until early in the morning, cooling the room temperature faster. This quiescent choice is one of the best for enhancing a building’s internal thermal performance while also possibly contributing to a decrease in operational energy consumption.